Respuesta :

Answer:

  • (-2, 13)
  • (1, 10)

=====================

Given system

  • y = x² + 9
  • x + y = 11

Substitute the value of y into second equation

  • x + x² + 9 = 11
  • x² + x - 2 = 0
  • x² +2x - x - 2 = 0
  • x(x + 2) - (x + 2) = 0
  • (x + 2)(x - 1) = 0
  • x + 2 = 0 and x - 1 = 0
  • x = - 2 and x = 1

Find the value of y

  • x = -2y = 11 - (-2) = 13
  • x = 1y = 11 - 1 = 10

Answer:

[tex](x,y)=\left(\; \boxed{-2,13} \; \right)\quad \textsf{(smaller $x$-value)}[/tex]

[tex](x,y)=\left(\; \boxed{1,10} \; \right)\quad \textsf{(larger $x$-value)}[/tex]

Step-by-step explanation:

Given system of equations:

[tex]\begin{cases}\phantom{bbbb}y=x^2+9\\x+y=11\end{cases}[/tex]

To solve by the method of substitution, rearrange the second equation to make y the subject:

[tex]\implies y=11-x[/tex]

Substitute the found expression for y into the first equation and rearrange so that the equation equals zero:

[tex]\begin{aligned}y=11-x \implies 11-x&=x^2+9\\x^2+9&=11-x\\x^2+9+x&=11\\x^2+x-2&=0\end{aligned}[/tex]

Factor the quadratic:

[tex]\begin{aligned}x^2+x-2&=0\\x^2+2x-x-2&=0\\x(x+2)-1(x+2)&=0\\(x-1)(x+2)&=0\end{aligned}[/tex]

Apply the zero-product property and solve for x:

[tex]\implies x-1=0 \implies x=1[/tex]

[tex]\implies x+2=0 \implies x=-2[/tex]

Substitute the found values of x into the second equation and solve for y:

[tex]\begin{aligned}x=1 \implies 1+y&=11\\y&=11-1\\y&=10\end{aligned}[/tex]

[tex]\begin{aligned}x=-2 \implies -2+y&=11\\y&=11+2\\y&=13\end{aligned}[/tex]

Therefore, the solutions are:

[tex](x,y)=\left(\; \boxed{-2,13} \; \right)\quad \textsf{(smaller $x$-value)}[/tex]

[tex](x,y)=\left(\; \boxed{1,10} \; \right)\quad \textsf{(larger $x$-value)}[/tex]

ACCESS MORE